2006
DOI: 10.1186/1744-9081-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation elicited by unrecognized stimuli

Abstract: BackgroundIt is unclear whether a stimulus that cannot be recognized consciously, could elicit a well-processed cognitive response.MethodsWe used functional imaging to examine the pattern of cortical activation elicited by unrecognized stimuli during memory processing. Subjects were given a recognition task using recognizable and non-recognizable subliminal stimuli.ResultsUnrecognized stimuli activated the cortical areas that are associated with retrieval attempt (left prefrontal), and novelty detection (left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Abnormal IPS activation in children with MLD has also been observed in a range of tasks that involve the processing of numerical information. For example, abnormal activation has been noted in tasks requiring children to perform approximate calculation (Kucian et al, 2006) and exact arithmetic (Ashkenazi et al, 2012; Berteletti et al, 2014). Impairments have also been observed in symbolic (Mussolin et al, 2010) and non-symbolic number comparison tasks (Price et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal IPS activation in children with MLD has also been observed in a range of tasks that involve the processing of numerical information. For example, abnormal activation has been noted in tasks requiring children to perform approximate calculation (Kucian et al, 2006) and exact arithmetic (Ashkenazi et al, 2012; Berteletti et al, 2014). Impairments have also been observed in symbolic (Mussolin et al, 2010) and non-symbolic number comparison tasks (Price et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found abnormal functional connectivity between the IPS and various fronto-parietal regions in children with MLD (Jolles et al, 2016; Rosenberg-Lee et al, 2015). Finally, activity in the IPS during the processing of numerical and arithmetic stimuli differs between children with and without MLD (Ashkenazi et al, 2012; Iuculano et al, 2015; Rosenberg-Lee et al, 2015; Berteletti et al, 2014; Price et al, 2007; Kucian et al, 2006). The IPS has long been linked to the representation of approximate numerical information in animals and healthy individuals (Ansari, 2008).…”
Section: Introductionmentioning
confidence: 99%